Voluntary co-consumption of alcohol and nicotine: Effects of abstinence, intermittency, and withdrawal in mice. (October 2016) - O'Rourke, Kyu Y.; Touchette, Jillienne C.; Hartell, Elizabeth C.; Bade, Elizabeth J.; Lee, Anna M.
Abstract: Alcohol and nicotine are often used together, and there is a high rate of co-occurrence between alcohol and nicotine addiction. Most animal models studying alcohol and nicotine interactions have utilized passive drug administration, which may not be relevant to human co-addiction. In addition, the interactions between alcohol and nicotine in female animals have been understudied, as most studies have used male animals. To address these issues, we developed models of alcohol and nicotine co-consumption in male and female mice that utilized voluntary, oral consumption of unsweetened alcohol, nicotine and water. We first examined drug consumption and preference in single-drug, sequential alcohol and nicotine consumption tests in male and female C57BL/6 and DBA/2J mice. We then tested chronic continuous and intermittent access alcohol and nicotine co-consumption procedures. We found that male and female C57BL/6 mice readily co-consumed unsweetened alcohol and nicotine. In our continuous co-consumption procedures, we found that varying the available nicotine concentration during an alcohol abstinence period affected compensatory nicotine consumption during alcohol abstinence, and affected rebound alcohol consumption when alcohol was re-introduced. Consumption of alcohol and nicotine in an intermittent co-consumption procedure produced higher alcohol consumption levels, but not nicotine consumption levels, compared with the continuous co-consumption procedures. Finally, we found that intermittent alcohol and nicotine co-consumption resulted in physical dependence. Our data show that these voluntary co-consumption procedures can be easily performed in mice and can be used to study behavioral interactions between alcohol and nicotine consumption, which may better model human alcohol and nicotine co-addiction. Highlights: Nicotine concentration affects nicotine consumption during alcohol abstinence. Alcohol abstinence results in elevated consumption after re-introduction. Chronic, intermittent co-consumption results in physical dependence in mice. Alcohol, but not nicotine consumption, is higher in intermittent co-consumption in males. In male mice, alcohol consumption is reduced when co-consumed with nicotine.